Age-related Comparison of Hip Joint Morphology in Isolated Femur Neck Fractures - Kamacı, Saygin; Bakırcıoğlu, Sancar; Çaglar, Ömür; Atilla, Bülent; Tokgözoğlu, A. Mazhar (Acta Medica, 2022)
Objective: Femoral neck fractures mostly occurs due to high-energy trauma in young population and management differs compared to elderly. Different geometric parameters in the hip joint can play a role in fracture morphology regarding to the age. Present study aims to compare hip morphology between young and elderly population Materials and methods: 45 patients with isolated femoral neck fracture included to the study. Patients were divided into two regarding to the age; group 1 (younger than 60 yr.) and group 2 (older than 60 yr.). Garden and Pauwels classifications, Sharp angle (acetabular index-AI), acetabular depth (AD), Hip-axis length (HLA), Neck-shaft angle (NSA), Center-edge angle (CE), Singh indexes and femur head extrusion indexes were compared between groups. Results: The mean age of group 1 (22 patients) was 48 ± 10.4 while the mean age of group 2 (23 patients) was 77 ± 6.3. Significant differences found in 3 parameters; the mean HLA (13.4 ± 1.4 cm vs 12 ± 1.1 cm) (p: 0,034), the Sharp angle (37.9° ± 5° vs 40.3° ± 3°) (p: 0.047) and the CE (38.1° ± 6.2° vs 34.8° ± 4.5°) (p: 0.48) between group 1 and 2 respectively. No statistically significant difference was found in terms of AD, NSA, Singh index and extrusion index. Conclusions: Our study shows influence of proximal femoral and acetabular morphology on femoral neck fracture in young patients and may help future studies to reveal the relevance between hip morphology and fractures type.